Trophic State of The Sungai Paku Reservoir Kampar Kiri District Kampar Regency Riau Province Based on TSI (Trophic State Index) - Tamba, Niger Efafras; Simarmata, Asmika Harnalin; Dahril, Tengku (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractTrophic State Index can be used to determine the trophic state of waters. The TSI used physical, chemical and biological approaches to determine the trophic state and the result will be more representative for analyzing the trophical state of waters. To understand the trophic state of the Sungai PakuReservoir, a research has been conducted in May - June 2019. There were three sampling stations, namely station 1 (riverin zone), station 2 (transition zone) and station 3 (lakustrin zone). In each sampling station there were 3 sampling point of depth, in the surface, in 2 Secchi depth, and in 4 Secchi depth. Sampling were conducted 3 times, once week. Water quality parameter measured were total phosphorus, chlorophyll-a, transparency, temperature, pH, dissolved oxygen and Nitrate. Trophic status was calculated based on Carlson Trophic State Index (TSI). The water quality parameter values were as follows: transparency: 69.2 - 80.8 cm, total phosphorus: 0.056 - 0.176 mg/L, chlorophyll-a: 1.753 - 3.372µg/L, depth: 69.2 - 80.8 cm, temperature: 28 - 30oC, pH: 5, dissolved oxygen: 2.08 - 5.74 mg/L and nitrate: 0.08 -0.11 mg/L. Trophic State Index value of the Sungai PakuReservoir was 54.49 - 59.57, it can be categorie as light eutrophic .Keywords: Water Quality, Reservoir, Light Eutrophic